2015
DOI: 10.1590/1808-057x201500090
|View full text |Cite
|
Sign up to set email alerts
|

Main Consequences of IFRS Adoption: Analysis of Existing Literature and Suggestions for Further Research

Abstract: <p>This study characterizes the results of scientific research on the effect of adopting the International Financial Reporting Standards (IFRS) that have been published in the most prestigious scientific journals in the field of accounting at the international level and it identifies avenues for further research. Based on the analysis of a set of 67 articles published by the accounting journals that make up the Social Sciences Citation Index (SSCI), published between 2000 and 2013, it is concluded that, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 90 publications
(133 reference statements)
3
23
0
9
Order By: Relevance
“…From the reading and analysis of this work we can conclude, in a general way, that the two hypotheses that we wished to test are confirmed. Specifically we confirm, coinciding with Brown (2011), Estima and Mota (2015), ICAEW (2015), and Kim et al (2016), among others, that the degree of knowledge that Spanish professionals have about the new accounting regulations increases in general with the passage of time and the development of the same regulations. And, on the other hand, and in this case coinciding with Milanés and Texeira (2006), Marín et al (2008), and Beusenlinck et al (2017), among others, that the degree of knowledge of professionals about the new accounting regulations in Spain, although increasing with the passage of time, is determined by the type of problem they face.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…From the reading and analysis of this work we can conclude, in a general way, that the two hypotheses that we wished to test are confirmed. Specifically we confirm, coinciding with Brown (2011), Estima and Mota (2015), ICAEW (2015), and Kim et al (2016), among others, that the degree of knowledge that Spanish professionals have about the new accounting regulations increases in general with the passage of time and the development of the same regulations. And, on the other hand, and in this case coinciding with Milanés and Texeira (2006), Marín et al (2008), and Beusenlinck et al (2017), among others, that the degree of knowledge of professionals about the new accounting regulations in Spain, although increasing with the passage of time, is determined by the type of problem they face.…”
Section: Discussionsupporting
confidence: 80%
“…One of the main characteristics of any transition is that professionals learn with time (ICAEW, 2015), even though they were initially trained and, in addition, IFRS are not static, and therefore early results on the implementation of the standard may not be sustained over time, since, in the face of change, behavior does not adjust so quickly (Brown, 2011). Estima and Mota (2015) point out that the consequences of the adoption of IFRS will probably begin to be detected after many years of their application. This progress is linked to the degree of knowledge that professionals have about all aspects of the new standards.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several past studies have identified IFRS adoption to be amongst the important factors which contributes towards economic growth of a country (Larson & Kenny 1995;Zaidi & Huerta2014). In general, past studies on IFRS adoption suggested that IFRS adoption leads to improved transparency (Ball 2006;Lambert, Leuz & Verrecchia 2007;Christensen, Glover & Wood 2012;Lourenço & Branco 2015). Indeed, they believed that transparency improvement leads to reduce information uncertainty, information asymmetry, cost of equity capital and leads to better risk estimations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although FDI has been identified as an economic consequences of IFRS adoption (Samaha & Khlif 2016;Utama, Farahmita & Anggraita 2016), very few studies have addressed this issue in greater detail (Zeghal & Mhedhbi 2006;Gordon et al 2012;Brüggemann, Hitz & Sellhorn 2013;Lourenço & Branco 2015). Most studies that looked at economics consequence of IFRS adoption tend to focus on cost of equity capital (CEC) (Daske, Hail, Leuz & Verdi 2008;Castillo-merino, Menéndez-plans & Orgaz 2014;Utama et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…As empirical research on the consequences of IFRS adoption worldwide develops, the context‐specificity of the effects of said adoption becomes increasingly clear (Soderstrom and Sun ; Brown ; Pope and McLeay ; Brüggemann et al. ; Palea ; Brown ; Lourenço and Branco ). There is currently some consensus surrounding the idea that rigorous enforcement mechanisms and reporting incentives are indispensable to the realisation of the expected benefits of IFRS adoption (e.g., Ball ; Leuz ; Brown ; Barth et al.…”
mentioning
confidence: 99%